a+b+c=6 then find (2-a)3+(2-b)3+(2-c)3-3(2-a)(2-b)(2-c)
Answers
Answered by
1
Hello!
Here is your answer
Given
![a + b + c = 6 a + b + c = 6](https://tex.z-dn.net/?f=a+%2B+b+%2B+c+%3D+6)
Let
2 - a = x
2 - b = y
2 - c = z
![x + y + z = 2 - a + 2 - b + 2 - c x + y + z = 2 - a + 2 - b + 2 - c](https://tex.z-dn.net/?f=x+%2B+y+%2B+z+%3D+2+-+a+%2B+2+-+b+%2B+2+-+c)
![x + y + z = 6 - a - b - c x + y + z = 6 - a - b - c](https://tex.z-dn.net/?f=x+%2B+y+%2B+z+%3D+6+-+a+-+b+-+c)
![x + y + z = 6 - (a + b + c) x + y + z = 6 - (a + b + c)](https://tex.z-dn.net/?f=x+%2B+y+%2B+z+%3D+6+-+%28a+%2B+b+%2B+c%29)
![x + y + z = 6 - 6 = 0 x + y + z = 6 - 6 = 0](https://tex.z-dn.net/?f=x+%2B+y+%2B+z+%3D+6+-+6+%3D+0)
If
![x + y + z = 0 \\ then \\ x {}^{3} + y {}^{3 } +z {}^{3} = 3xyz x + y + z = 0 \\ then \\ x {}^{3} + y {}^{3 } +z {}^{3} = 3xyz](https://tex.z-dn.net/?f=x+%2B+y+%2B+z+%3D+0+%5C%5C+then+%5C%5C+x+%7B%7D%5E%7B3%7D++%2B+y+%7B%7D%5E%7B3++%7D++%2Bz+%7B%7D%5E%7B3%7D++%3D+3xyz)
![xyz =( 2 - a)(2 - b)(2 - c) xyz =( 2 - a)(2 - b)(2 - c)](https://tex.z-dn.net/?f=xyz+%3D%28+2+-+a%29%282+-+b%29%282+-+c%29)
![+ 3xyz - 3xyz = 0 + 3xyz - 3xyz = 0](https://tex.z-dn.net/?f=+%2B+3xyz+-+3xyz+%3D+0)
Answer = 0
Here is your answer
Given
Let
2 - a = x
2 - b = y
2 - c = z
If
Answer = 0
Similar questions
English,
8 months ago
English,
8 months ago
Geography,
8 months ago
Math,
1 year ago
Political Science,
1 year ago
Social Sciences,
1 year ago
Science,
1 year ago